Metafora haiwan: kajian perbandingan bahasa Melayu dan bahasa Indonesia (Jurnal Bahasa, 2022)
This article discusses the usage of animal metaphors in Malay and Indonesian focusing on linguistic features including semantics, forms and formations, and concepts. Malay metaphors were collected from general dictionaries and dictionaries of idioms and proverbs from Malaysia and Indonesia. This descriptive study adopts the theory of conceptual metaphor from Lakoff and Johnson (2008) which holds that conceptual metaphors shape not just our communication but also the way we think and act. The study finds that the Malay societies in Malaysia and Indonesian each create animal metaphors with the same meanings because the two societies have similar thought concepts resulting from their close cultural relations.